Piperacillin/tazobactam-induced neurotoxicity in a hemodialysis patient: a case report - Neves, Precil Diego Miranda de Menezes [UNESP]; Freitas, Fernanda Moreira de [UNESP]; Kojima, Christiane Akemi [UNESP]; Carmello, Beatriz Leone [UNESP]; Bazan, Rodrigo [UNESP]; Barretti, Pasqual [UNESP]; Martin, Luis Cuadrado [UNESP] (Wiley, 2015)
Antibiotics are potentially a cause of neurotoxicity in dialysis patients, the most common are thebeta-lactams as ceftazidime and cefepime, and few cases have been reported after piperacillin/tazobactam use. This report presents a case of a hypertensive and diabetic 67-year-old woman inregular hemodialysis, which previously had a stroke. She was hospitalized presenting pneumonia,which was initially treated with cefepime. Two days after treatment, she presented dysarthria, lefthemiparesis, ataxia, and IX and X cranial nerves paresis. Computed tomography showed no acutelesions and cefepime neurotoxicity was hypothesized, and the antibiotic was replaced bypiperacillin/tazobactam. The neurologic signs disappeared; however, 4 days after with piperacillin/tazobactam treatment, the neurological manifestations returned. A new computed tomographyshowed no new lesions, and the second antibiotic regimen withdrawn. After two hemodialysissessions, the patient completely recovered from neurological manifestations. The patient presentedsequentially neurotoxicity caused by two beta-lactams antibiotics. This report meant to alertclinicians that these antibiotics have dangerous neurological effects in chronic kidney diseasepatients.
Keywords: Chronic kidney disease; Hemodialysis; Neurotoxicity; Piperacillin/tazobactam